2015
DOI: 10.1038/sc.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Time-series analysis of the barriers for admission into a spinal rehabilitation unit

Abstract: Study design: This is a prospective open-cohort case series. Objectives: The objective of this study was to assess changes over time in the duration of key acute hospital process barriers for patients with spinal cord damage (SCD) from admission until transfer into spinal rehabilitation unit (SRU) or other destinations. Setting: The study was conducted in Acute hospitals, Victoria, Australia (2006. Methods: Duration of the following discrete sequential processes was measured: acute hospital admission until ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…It is suggested that a formal study needs to be undertaken to determine the validity of the ISNCSCI among people with SCDys and to help with formulating guiding principles that may be appropriate to optimize the validity for adjust for confounding variables and computer modeling. 58,59 In addition, systematic and scoping reviews, along with meta-analyses when sufficient studies are available, can be used to increase the evidence base regarding SCDys.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…It is suggested that a formal study needs to be undertaken to determine the validity of the ISNCSCI among people with SCDys and to help with formulating guiding principles that may be appropriate to optimize the validity for adjust for confounding variables and computer modeling. 58,59 In addition, systematic and scoping reviews, along with meta-analyses when sufficient studies are available, can be used to increase the evidence base regarding SCDys.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…6 Patients may have received treatment outside of specialized rehabilitation facilities due to personal choice, admission criteria, absence of local treatment facilities available for persons with NTSCD, lengthy wait-times, and/or death prior to rehabilitation facility admission. 11,22,23 Survey data use assumptions when extrapolating to overall population risks, as there is an inherent bias toward persons who have less severe injuries, 24 higher socioeconomic status, 25 and non-terminal diagnoses. 24 An approach beyond a single point of care and survey-based data is required to assess a more inclusive sample population for NTSCD.…”
mentioning
confidence: 99%